Mapping of Soil Degradation Status on Various Land Slope in Paranggupito, Wonogiri - Mujiyo; Ahmad Norri Prasetyo; Aktavia Herawati; Dwi Priyo Ariyanto; Hery Widijanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Soil degradation causes in loss of soil function in supporting living things. The slope of the land has a potential to cause soil degradation. This study aims to provide scientific information on the status of soil degradation in the form of a map, and to provide recommendations for improvement based on the determinant factor. Land map units were determined by overlay of maps; soil type, rainfall, slope, and land use. Research area were divided into 12 LMU, and each of it was repeated by 3 site samplings. Analysis of soil degradation status accordings to Government Regulation of the Republic Indonesia. ANOVA was used to determine the effect of the land slope on the soil degradation status. Correlation analysis used to know the relationship between the parameters with soil degradation. The result shows the status of soil degradation is slightly degraded (R.I) in 6.032,44 ha (100% area research) with different limiting factors. Land slope 16-25% has the highest impact on soil degradation with the determinant parameters were bulk density and a total of porosity. Soil bulk density increases along with increasing steep slope. Efforts to improve the status of soil degradation are by giving organic matter and minimizing soil tillage.